2016
DOI: 10.1166/jnn.2016.12793
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transport Through Graphene Nanoribbons with Stone-Wales Reconstruction at Edges and Interfaces

Abstract: In this paper, we study the conductance of the graphene nanoribbons(GNRs) in the presence of the Stone-Wales(S-W) reconstruction, using the transfer matrix method. The ribbon is connected with semi-infinite quantum wires as the leads. The S-W reconstruction occurs on the edges and the interfaces between the electrodes and ribbon. When the reconstruction occurs on the edges, the conductance is suppressed considerably if the gate voltage Vg takes intermediate values around |Vg| ∼ t0(t0 being the hopping amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…This process is accompanied with a structural relaxation until the change in total energy and forces on carbon atoms become less than 10 -4 eV and 10 -3 eV/Å respectively [7]. As matter of fact, it is found that such a dislocation experimentally can be created by irradiation, chemical treatments and during a rapid quench from high temperature [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This process is accompanied with a structural relaxation until the change in total energy and forces on carbon atoms become less than 10 -4 eV and 10 -3 eV/Å respectively [7]. As matter of fact, it is found that such a dislocation experimentally can be created by irradiation, chemical treatments and during a rapid quench from high temperature [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%